Transformation of Polycythemia Vera into Acute Lymphoblastic Leukemia - Qasim, Zahida; Nasim, Lubna; Parveen, Roshan (International Journal of Pathology, 2018)
Transformation of Polycythemia Rubra Vera to acute lymphoblastic leukemia is extremely rare. A case of 22years old female is reported who developed acute lymphoblastic leukemia 17 years after the initial diagnosis ofPolycythemia Vera PV]. Analytical Immunocytochemistry confirmed Precursor B cell Acute LymphoblasticLeukemia( BALL) with expression of CD13 and showed gated population of 86% and Blast/atypical populationof weak CD45(92%), CD10+19(72%) and HLADR 87%. The rare occurrence of Acute Lymphoblastic Leukemia(ALL) in patients of Polycythemia Vera (PV) indicates clonal expansion of an abnormal uncommitted plueripotent,haemopoietic cell which results in polycythemia Vera (PV) disease phenotype